PALLIATIVE CARE IN THE YOUNG PERSON'S COMMUNITY: SUPPORT FOR SCHOOLS. Issue 1 (1st March 2014) - Craig, F; Kelly, P; Boden, C; Samuel, J
Abstract : Introduction: Being part of a school community, where young people develop peer relationships and experience a sense of their value in society, is integral to childhood/young adulthood. Supporting terminally ill young people to maintain a role within this community can be crucial to their overall well –being. Essential to this is the ability of school staff to support their physical and psychological health while in school, yet little is known about the support they require to facilitate this. Aim(s) and method(s): We utilised survey methods to investigate the confidence and support needs of school staff. Results: 78% of the target population completed the survey. In discussions with students, staff were confident ascertaining concerns about the effect of their condition on schooling and participation in activities, but less confident discussing concerns about illness, death and dying. In discussions with parents, staff were relatively confident exploring concerns the child might have about illness and dying and symptoms they may experience. However, they were less confident discussing the option of the child staying at school. Respondents identified meetings in school with Health Care Professional's, the availability of telephone advice during the school day and written medical plans amongst the most valuable forms of support. Conclusion(s): School staff are confident when talking to parents/students about symptom progression and impact on education, but are uncertain what this means in terms of school participation. HCP's must work directly with schools to provide real-time advice and written plans, to enable our patients to be supported within their school community.